Fasilitas Evaluasi yang Menggabungkan Pengukuran, Bimbingan dan Penilaian dalam Sistem e-Learning - Yuni Yamasari, (Jurnal Penelitian Pendidikan Matematika dan Sains, 2008)
This paper focuses on the evaluation in the e-learning system which is almost similar to the on-line testing. The difference between this research and other ones is that this research is combining the measurement, evaluation to the students so it is more accurate. This is because this evaluation is not just based on the right and wrong answer, but also what students had done to answer. This is very important because teachers are able to determine which students had had correct understanding. In addition, teachers are able to determine students which are able to follow the next level.